Application of ultrafiltration for backwash water pre-treatment for recirculation into an infiltration water treatment system - Małgorzata Wolska; Małgorzata Kabsch-Korbutowicz; Anna Solipiwko-Pieścik; Halina Urbańska-Kozłowska (Desalination and Water Treatment)
The need to reduce water consumption and to rationally manage water resources forces water utilities to minimalize water losses during water purification. Therefore, backwash water generated in the filtration process is increasingly the subject of research aimed at its reuse in the water purification system. The research presented here was conducted in a large infiltration water treatment plant with a capacity of 87,000 m3/d, and its subject was backwash water resulting from rinsing sand bed filters. The backwash water was pre-treated by an ultrafiltration process in a flow installation with a capacity of 100 l/h, using membrane modules with a PVDF spiral membrane (200 kDa) and a PES capillary membrane (80 kDa). The effectiveness of the process was assessed based on the degree of retention of organic substances, microorganisms including indicator ones, and the amount of iron and manganese compounds. Presence of the microorganisms and organic compounds could pose a health or technological threat when of recirculating backwash water into the water treatment system. Implementing recirculation pre-treated backwash water will allow for a reduction of environmental use costs, including the costs of water abstraction and wastewater discharge. While at the same time increasing the costs of water purification (backwash water pretreatment and pumping costs). It was estimated that the increase in water purification costs will not exceed 5 % of the current price. The 80 kDa capillary membrane was the most suitable for the pre-treatment of backwash water due to its effective elimination of microorganisms as well as iron and manganese compounds.